Development of a simplified dynamic testing device for turfed sports surfaces - Caple, M. C. J.; James, I. T.; Bartlett, M. D.; Bartlett, D. I. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2011)
The response of natural turf surfaces to loading changes with the force and loading rate applied. Quantification of surface behaviour to athlete loading is complicated by the lack of devices that replicate forces, stresses and loading rates of athletes that can be specifically used on natural turf. To address this issue, a vertical dynamic impact testing device, the DST, was developed. The DST consists of a compressed air-driven ram that vertically impacts a studded test foot on to the surface using data from biomechanical studies. The vertical dynamic stress of athlete foot strike during running is replicated, using peak force and mean boot contact area data. The ram pressure is adjustable to allow variation of the stress applied upon impact, potentially replicating a range of athlete-surface interactions.